On the determinants of international currency choice: Will the euro dominate the world? - Matteo Bobba; Giuseppe Della Corte; Andrew Powell (Inter-American Development Bank, Research Department, 2007)
Money is used as a store of value, a medium of exchange and a unit of account. Most recent analyses of currency choice in an international setting have focused on the denomination of reserves - the store of value role. However, public data are only aggregate and exclude several countries. This paper focuses on currency choice for the unit of account role, employing a detailed database on security issuance across countries, time and currencies. The paper finds a stable relation between currency choice and specific real and financial variables with different specifications for developed and developing countries, as well as evidence for persistence and network externalities. Exploiting the creation of the Euro, the paper finds a large and significant Euro liquidity effect at the cost of the dollar, especially in the early years of the life of the new currency. The estimates suggest that the Euro is making significant progress toward threatening the role of the dollar as the dominant international currency.
Keywords: F02; F31; F33; 330; currency composition; dominant international currency; liquidity effect